Cochlear implants in the management of hearing loss in Neurofibromatosis Type 2. (4th May 2017) - Harris, Frances; Tysome, James R.; Donnelly, Neil; Durie-Gair, Juliette; Crundwell, Gemma; Tam, Yu Chuen; Knight, Richard D; Vanat, Zebunnisa H.; Folland, Nicola; Axon, Patrick
Abstract : Objective: Review of cochlear implant (CI) outcomes in patients with Neurofibromatosis Type 2 (NF2), implanted in the presence of an ipsilateral vestibular schwannoma (VS). Hearing restoration was combined in some cases with a Bevacizumab regime. Method: Retrospective review of 12 patients, managed over the period 2009–2016, at a tertiary referral multidisciplinary NF2 clinic. The patients are grouped by hearing outcomes to explore likely protective factors, and to generate a proposed decision-making tool for the selection of either CI or Auditory Brainstem Implant (ABI). Results: Four of the 12 patients achieved speech discrimination without lip-reading. In these individuals there is reason to think that the mechanism of their hearing loss was cochlear dysfunction. A further four patients received benefit to lip-reading and awareness of environmental sound. For such patients their hearing loss may have been due to both cochlear and neural dysfunction. Two patients gained access to environmental sound only from their CI. Two patients derived no benefit from their CIs, which were subsequently explanted. Both these latter patients had had prior ipsilateral tumour surgery, one just before the CI insertion. Conclusion: Cochlear implantation can lead to open set speech discrimination in patients with NF2 in the presence of a stable VS. Use of promontory stimulation and intraoperative electrically evoked auditory brainstem response testing, along with case history, can inform the decision whether to implant an ABI or CI.